You need to evaluate the critical numbers of the function and for this reason, you must differentiate the function with respect to t, using the product and chain rules, such that:

`g'(t) = (t*sqrt(4 - t))'`

`g'(t) = t'*sqrt(4 - t) + t*(sqrt(4 - t))'`

`g'(t) = sqrt(4 - t)...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to evaluate the critical numbers of the function and for this reason, you must differentiate the function with respect to t, using the product and chain rules, such that:

`g'(t) = (t*sqrt(4 - t))'`

`g'(t) = t'*sqrt(4 - t) + t*(sqrt(4 - t))'`

`g'(t) = sqrt(4 - t) + t*((4-t)')/(2sqrt(4 - t))`

`g'(t) = sqrt(4 - t) + (-t)/(2sqrt(4 - t))`

You need to solve for t the equation g'(t) = 0:

`sqrt(4 - t) + (-t)/(2sqrt(4 - t)) = 0`

`2(4 - t) - t = 0 => 8 - 2t - t = 0 => 3t = 8 => t = 8/3`

**Hence, evaluating the critical values of the given function, yields `t = 8/3.` **